Relationship between the position at the end of the first lap and the final classification in XCO MTB - Pedro Vigário (Asociación Científica Internacional de Educación Física, 2021)
Cross-country mountain bike (XCO) elite competitions consist of several laps of a technical off-road course. At the start of a race, an MTB Cross-country (XCO) rider does not control his position on the grid, this is awarded first, according to his international ranking, and then according to the other conditions provided for in the regulations. However, his performance, immediately after the start and until the end of the first lap, can be trained. This study aimed to analyze the relationship between the position at the end of the first lap and the final classification in an XCO competition. The participants were high-level Portuguese athletes, of the Elite male category, who competed in national competitions held in Portugal between 2017 and 2020, aged ≥ 19 years. It was concluded that there is a very strong correlation between the position occupied by the riders at the end of the first lap and the final position in the race, mean=0,907 and p=0,006, which is statistically significant, therefore have important implications for training planning in XCO.